Emotion Contagion in Avatar-Mediated Group Interactions - Van Haeringen, Erik; Gerritsen, Charlotte (International Conference on Affective Computing and Intelligent Interaction and workshops, 2024)
Applications of emotionally expressive virtual humans in society are growing, often in the form of AI-driven autonomous agents. In this study however, we explore an application where virtual humans act as intermediaries in human-to-human communication, a type of application that has received significant attention but is not widely available yet. Specifically, participants communicate in a video call setting, where, instead of webcam footage, they observe others via human-like avatars. The avatars mimic in real-time the facial expressions of the person they represent. By contrasting this with a control condition where avatars do not mimic expressions, the study aims to test whether emotional expressions via avatars are contagious and drive collective emotion in a similar way as previously found for regular video calls. The recorded facial expressions of the participants are annotated manually and automatically, while the attention towards others in the group is recorded by tracking the gaze of the participants. We hypothesised emotion contagion would drive emotional convergence at the group level and in gaze pairs. The results show that the opposite may have taken place. Looking at the avatars of others was related to a decrease in similarity of facial expressions and emotional content of those expressions, compared to before the gaze. This was found both with and without mimicking avatars, yet more negative expressions were present in the control condition compared to the avatars that mimicked expressions. We discuss potential explanations and implications of these findings and make recommendations for future designs.